Literary criticism and theory : from Plato to postcolonialism - Goulimari, Pelagia (London ; New York : Routledge, Taylor & Francis Group, 2015)
"This incredibly useful volume offers an introduction to the history of literary criticism and theory from classical antiquity to the present. It is almost impossible to read or study literature without acknowledging its relationship to criticism and this guide shows how the two have been inextricable since Plato. Introducing theory and criticism through the texts themselves, Pelagia Goulimari examines: - A variety of key thinkers from Plato and Aristotle through to Foucault and Derrida - Topics and themes in the history of literary criticism such as mimesis and creation, inspiration, the emotions, reason, aesthetic, history, morality, ethics, culture and discourse - The main genres and movements in the history of literature including the epic, tragedy, comedy, romanticism, realism, modernism and postmodernism - Cross-historical connections between theories and theorists and the dissemination, appropriation and creative misunderstanding of concepts, ideas and arguments. With handy features such as a glossary, annotated further reading, descriptive text boxes and instructive marginalia this book is the ideal introduction to anyone approaching theory and criticism for the first time"--
Includes bibliographical references (pages 340-362) and index.
Includes bibliographical references and index.
Keywords: Criticism -- History; Literature -- History and criticism -- Theory, etc; Literature -- Philosophy -- History; LITERARY CRITICISM / General; LITERARY CRITICISM / Semiotics & Theory